Are lopinavir and efavirenz serum concentrations in HIV-infected children in the therapeutic range in clinical practice?. (May 2014) - Bibra, Mirjam von; Rosenkranz, Bernd; Pretorius, Erina; Rabie, Helena; Edson, Claire; Lenker, Ulrike; Cotton, Mark; Klinker, Hartwig
<x content-type="archive" xml:space="preserve">Abstract</x> Background: In antiretroviral treatment the role of therapeutic drug monitoring via measurement of serum levels remains unclear, especially in children. Aim: To quantify exposure to LPV and EFV in children receiving therapy in a routine clinical setting in order to identify risk factors associated with inadequate drug exposure. Method: A prospective study was conducted in a routine clinical setting in Tygerberg Children's Hospital, South Africa. A total of 53 random serum levels were analyzed. Serum concentrations were determined by an established high-performance liquid chromatography method. Results: Of 53 HIV-infected children treated with lopinavir (n = 29, median age 1·83 y) or efavirenz (n = 24, median age 9·3 years), 12 showed serum levels outside the therapeutic range (efavirenz) or below Cmin (lopinavir). Low bodyweight, rifampicin co-treatment, and significant comorbidity were potential risk factors for inadequate drug exposure. Conclusion: These findings, together with previous studies, indicate that therapeutic drug monitoring can improve the management of antiretroviral therapy in children at risk.